Respuesta :

Answer:

- 10

Step-by-step explanation:

Distribute the '+' into the '-' and simplify:  

-5+9+(-5)+(-10)+(1) =

-5 + 9 - 5 - 10 + 1 =

-10

Answer:

[tex] \boxed{ \boxed{ \bold{ \purple{ - 10}}}}[/tex]

Step-by-step explanation:

[tex] \sf{ - 5 + 9 + ( - 5) + ( - 10) + 1}[/tex]

When there is a ( + ) in front of an expression in parentheses, the expression remains in same.

⇒[tex] \sf{ - 5 + 9 -5 - 10 + 1}[/tex]

Calculate

⇒[tex] \sf{ 4 - 5 - 10 + 1}[/tex]

⇒[tex] \sf{ - 1 - 10 + 1}[/tex]

⇒[tex] \sf{ - 11 + 1}[/tex]

⇒[tex] \sf{ - 10}[/tex]

Hope I helped!

Best regards!!